Penampilan Kualitas Kimia Susu Sapi Perah Laktasi Dengan Ransum Yang Disuplementasi Daun Lamtoro - Dimas Fajar Nugroho; Astari Ratnaduhita (Fakultas Pertanian Universitas Veteran Bangun Nusantara Sukoharjo, 2022)
This study aims to investigate the chemical characteristics of dairy cow who received feed rations with lamtoro leaf supplementation included milk production, milk fat content, milk protein content, and lean solids (SNF) (lactoscan method). The experiment was designed followed completely randomized design, consisted of 4 treatments, namely P0, P1 and P2 with 3 replications PFH cows, namely P0, P1, P2, P3 and P3 with 3 repeats. The control ration used in this research was the daily ration given to dairy cows at the breeder, consisting of elephant grass, tofu dregs and basal concentrate (consisting of rice bran, pollard, coffee husk, coconut cake, vitamins and minerals). The experiment was performed for 60 days, with 12 lactation cows at body weight 400 kg. Cows were at 6 to 7 months of lactation stage. The results of this study indicate that there is an increase in the chemical quality of milk which includes protein content (P0:2.73%, P1:3.01%, P2:3.1%, P3:3.25%), fat content (P0:2 0.08%, P1:2.98%, P2:3.03%, P3:3.04%) and solid non-fat content (SNF) (P0:7.80%, P1:7.79%, P2: 8.09%, P3:7.65%). Analysis of variance showed that all data on the chemical quality of dairy cow's milk had a significant effect (P<0.05). Conclusion The conclusion of this research is the addition of lamtoro leaf supplementation by 10% of the total forage of lactated Friesian Holstein crossbreed dairy cows can improve the chemical quality of milk which includes protein content, fat content and solid non fat content (SNF) of milk.